Markups, Returns to Scale, and Productivity: A Case Study of Singapore's Manufacturing Sector - Kee, Hiau Looi (World Bank, Washington, D.C., 2013)
The results of this paper challenge the conventional wisdom in the literature that productivity plays no role in the economic development of Singapore. Properly accounting for market power and returns to scale technology, the estimated average productivity growth is twice as large as the conventional total factor productivity (TFP) measures. Using a standard growth accounting (production function) technique, Young (1992, 1995) found no sign of TFP growth in the aggregate economy and the manufacturing sector of Singapore. Based on Young's results, Krugman (1994) claimed that there was no East Asia miracle as all the economic growth in Singapore could be attributed to its capital accumulation in the past three decades. Citing evidence on nondiminishing market rates of return to capital investment in Singapore during the period of fast growth as an indication of high productivity growth, Hsieh (1999) challenged Young's findings using the dual approach. But all of these papers maintained the assumptions of perfect competition and constant returns to scale and used only aggregate macro-level data. Kee uses industry level data and focuses on Singapore's manufacturing sector. She develops an empirical methodology to estimate industry productivity growth in the presence of market power and nonconstant returns to scale. The estimation of industry markups and returns to scale in this paper combines both the production function (primal) and the cost function (dual) approaches while controlling for input endogeneity and selection bias. The results of a fixed effect panel regression show that all industries in the manufacturing sector violate at least one of the two assumptions. Relaxing the assumptions leads to an estimated productivity growth that is on average twice as large as the conventional TFP calculation. Kee concludes that productivity growth plays a nontrivial role in the manufacturing sector.